A CAN based distributed telemetry and telecommand network for a nanosatellite - Khumalo, Simphiwe (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2008.